Design of a new type of deep hole boring device. Issue 6 (January 2021) - Cai, Hao; Dong, Zhen; Zhang, Zhi Bing; Cui, Shuai
Abstract: When boring deep holes, as the workpiece hole becomes deeper and deeper, the size of the boring bar is large, the overhang is large, the vibration of the boring bar is large, and it is easy to deform, which makes the ordinary deep hole boring tool unable to meet the actual complex working conditions. In order to reduce the vibration and deformation of the boring bar and further improve the machining accuracy of the workpiece, a deep hole boring device with auxiliary support is designed. The adjustable support provided by the device can play a role of fixing and guiding during processing, thereby effectively reducing processing vibration and deformation and improving processing accuracy. And completed the trial production and processing experiment of the device prototype. The results show that the machining accuracy of the new cylindrical deep hole boring device is very high and meets the design requirements.